Impact of garlic polysulfide supplementation on biochemical and hematological parameters in dairy cows - Nedić Sreten; Gajić Mirjana; Bošnjaković Dušan; Vujanac Ivan; Prodanović Radiša; Bojkovski Jovan; Mitrović Aleksandra; Milenković Milan; Manojlović Dragan; Jovanović Ljubomir; Kirovski Danijela; Arsić Sveta (Veterinarski Glasnik)
In recent years, there have been numerous research activities related to the use of different herbal agents, especially those originating from chestnuts and garlic, as alternatives to synthetic growth promoters like antibiotics. Garlic and its active ingredients have been studied for their potential benefits, such as improving feed intake, production performance, rumen fermentation, and udder health. The aim of our study was to investigate the influence of garlic polysulfides, including diallyl polysulfide and dipropyl polysulfide, on hematological and biochemical parameters in dairy cows, as well as their possible effect on subclinical mastitis therapy. Eighteen late lactation Holstein cows were divided into three numerically equal groups (n=6): CON (non-supplemented cows), ALL (supplemented with 1000 mg/day of diallyl polysulfide), and PRP (supplemented with 1000 mg/day of dipropyl polysulfide). Blood sampling for hematological and biochemical analyses as well as the California mastitis test (CMT) test were performed before and after the 15-day study. The results showed that garlic supplementation significantly increased blood leukocyte count and blood glucose concentration (p<0.05, respectively), and significantly decreased blood urea concentration (p<0.05) after the 15-day trial in both ALL and PRP groups compared with the day 0. In the supplemented groups, the CMT score was significantly lower (p<0.05, respectively) after the 15-day treatment compared with the CON group. The use of different mixtures of biologically active garlic polysulfides in the diet could improve immune and metabolic status, as well as support mastitis treatments in dairy cows.